2020
DOI: 10.1108/bfj-10-2019-0773
|View full text |Cite
|
Sign up to set email alerts
|

Partial substitution of whole wheat with acha and pigeon pea flours influences rheological properties of composite flours and quality of bread

Abstract: PurposeWheat flour (whole grain or white wheat flour) is a major ingredient for production of baked goods and confectionery products in Nigeria. However, due to unfavourable climatic and soil conditions, there is over-dependence on importation of wheat having a negative impact on the nation's gross domestic product (GDP). This has therefore spurred increasing popularity of partial or full replacement of wheat flour with other flour types for economic or nutritional reasons. Therefore, the purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 39 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…Most of the lentil starches represent a large oval/elliptical to round shape granules possessing crackles and even flat surface, whereas bean and pea starches are characterized as deep circles having a small slash at center or a notch at one end. The morphology of starch granules changes according to the legume type, the concentration of synthetic enzymes during biosynthesis of the starch molecule, its membrane structure, and association of these molecules (Ashogbon et al, 2011; Olagunju et al, 2020). Characteristically, lentil starch granule diameter ranges from 3 to 30 μm (Sotomayor et al, 1999; Ahmed et al, 2016; Romero & Zhang, 2019), but heterogeneous sizes are 19–35 μm long and 14–22 μm wide (Ma et al, 2011).…”
Section: Microstructuresmentioning
confidence: 99%
“…Most of the lentil starches represent a large oval/elliptical to round shape granules possessing crackles and even flat surface, whereas bean and pea starches are characterized as deep circles having a small slash at center or a notch at one end. The morphology of starch granules changes according to the legume type, the concentration of synthetic enzymes during biosynthesis of the starch molecule, its membrane structure, and association of these molecules (Ashogbon et al, 2011; Olagunju et al, 2020). Characteristically, lentil starch granule diameter ranges from 3 to 30 μm (Sotomayor et al, 1999; Ahmed et al, 2016; Romero & Zhang, 2019), but heterogeneous sizes are 19–35 μm long and 14–22 μm wide (Ma et al, 2011).…”
Section: Microstructuresmentioning
confidence: 99%
“…The addition increased the protein contents with improved profile of essential amino acids. However, sensory analysis showed that the eating quality of the breads made from the composite flours was less than that of pure wheat flour Olagunju et al, 2020 Sourdough bread White fonio Fonio and bambara nut flours at a ratio of 1:1 were made into sourdough by fermentation. The sourdough up to 30% was mixed with wheat flour to make sourdough breads.…”
Section: Fonio Type Major Findings Referencesmentioning
confidence: 99%
“…White fonio flour was mixed into wheat flour to make breads, biscuits, and sugar cookies (Ayo & Nkama, 2004; Chinma et al., 2016; Drábková, Hrušková, & Švec, 2017; Inyang et al., 2018; McWatters et al., 2003; Olagunju, Ekeogu, & Bamisi, 2020; Švec & Hrušková, 2018). Increasing fonio flour proportion increased the water absorption and decreased the loaf volume and the sensory quality of the bread (Ayo & Nkama, 2004).…”
Section: Food and Other Applications Of Fonio And Fonio Componentsmentioning
confidence: 99%
See 2 more Smart Citations